Analisis pengelolaan barang milik daerah dan hubungannya dengan pendapatan daerah Provinsi Jambi - zaki, Achmad; Hidayat, Syurya; Syaparuddin, Syaparuddin (Jurnal Paradigma Ekonomika, 2020)
The objectives of this study were 1) To analyze BMD management by the Jambi Provincial Government in accordance with Permendagri No. 19 of 2016. 2) To analyze the potential for saving APBD in the Jambi Provincial Government in the management of BMD. 3) To identify and analyze the factors that influence the level of savings in BMD management in the Jambi Provincial Government. 4) To know and analyze the relationship between APBD savings from the elimination of BMD and regional revenues of Jambi Province, and 5) To analyze the strategies that the government should take in an effort to eliminate BMD for saving BMD maintenance costs in the Jambi Provincial Government. The analytical tool used is multiple linear regression, correlation, and SWOT analysis. Based on the results of the research that the implementation has been carried out in accordance with Permendagri No. 19 of 2016 is planning needs and budgeting, procurement, acceptance, storage, and distribution, utilization, security, assessment, transfer, and compensation claims. Partially the leadership, attitude, and policy variables have a significant effect on the savings variable. The result of the correlation shows that the saving value has a moderate relationship with the regional income of Jambi Province. Based on the results of the SWOT matrix analysis in eliminating BMD, namely recruiting HR, maintaining the completeness of BMD ownership documents, and providing additional incentives for BMD management staff.